Biomechanical optimization of the far cortical locking technique for early healing of distal femur fractures. (March 2021) - Sarwar, Ahmed; Gee, Aaron; Bougherara, Habiba; Kuzyk, Paul R.T.; Schemitsch, Emil H.; Zdero, Radovan
Highlights: Far cortical locking (FCL) screws aid early callus formation for fracture plating. Biomechanical effects of FCL screw number, distribution, and diameter were assessed. Finite element modeling was used to analyze all possible FCL screw configurations. Axial interfragmentary motion, bone stress, and hardware stress were computed. Results showed a family of curves for all biomechanical properties. Abstract: This finite element study optimized far cortical locking (FCL) technology for early callus formation in distal femur fracture fixation with a 9-hole plate using FCL screws proximal to, and standard locking screws distal to, the fracture. Analyses were done for 120 possible FCL screw configurations by varying FCL screw distribution and number. A hip joint force of 700 N (i.e. 100% x body weight) was used, which corresponds to a typical 140 N "toe-touch" foot-to-ground force (i.e. 20% x body weight) suggested to patients immediately after surgery. Increased FCL screw distribution (i.e. shorter plate working length) caused a decrease at the medial side and an increase at the lateral side of the axial interfragmentary motion (AIM), mildly affected shaft and condylar cortex Von Mises max stress (σMAX ), increased plate σMAX, and decreased shaft FCL screw and condylar locking screw σMAX . Increased FCL screw number decreased AIM and σMAX on the shaft cortex, condylar cortex, plate, and FCL screws, but not condylar screws. The optimal FCL screw configuration had 3 FCL screws in plate holes #1, 5, and 6 (proximal to distal) for optimal AIM of 0.2 - 1 mm and reduce shear fracture motion, thereby encouraging early callus formation.